CORRELATION EMERGENCY STATUS WITH ATTENDANCE OF EMERGENCY ROOM AT RSUD IBNU SINA KABUPATEN GRESIK - Hardyanti, Hikmah Ridho; Chalidyanto, Djazuly (Jurnal Administrasi Kesehatan Indonesia, 2015)
ABSTRACT The number of non-emergency patients is high from normative visit an indication of problems in the Emergency Room. The purpose of this study to analyze the relationship between the patients assessment of the provider or hospital with emergency status. This study examines the factors that exist in hospitals, among others, policy about patients who come, the physical condition of buildings, facilities, skilled human resources. The study involved 172 patients who ever went to the Emergency Room RSUD Ibnu Sina Kabupaten Gresik in June 2014, data were taken with visit their homes to conduct interviews based on a questionnaire. The independent variable in this study is the emergency of the patients status while the dependent variable is the policy of the patients who come, the physical condition of buildings, facilities, skilled human resources. Data were analyzed using the relationship test Chi-square (α = 0.05). The study states that the factors comprising hospital policy on patients who come, the physical condition of buildings, facilities and skilled human resources and discipline to have a relationship with the emergency of the patients status. Variable physical condition of buildings, facilities and skilled human resources need to be considered and improved the quality of emergency services. Keywords: facilities, hospital, status of emergency, the physical condition of                    buildings